(untitled) (SS Multidisciplinary Research Journal, 2024)
Rainbow trout farming is a relatively new industry in Nepal. It is possible in Nepal around the year under natural environmental conditions. In terms of social and economic points of view, trout farming is beneficial for farmers due to the availability of a natural cold stream and the existence of a favorable environment. Finding out the opportunities and challenges of rainbow trout farming in Helambu rural Municipality is the main concern of this article. It is based on both primary and secondary sources of data. Primary data were collected through interviews with 3 farmers involved in trout farming. Due to its rich source of nutrition, alternative source of income, and high commercial value, it has high prospects. Due to climate change, lack of experienced labor, and an imperfect market, it has challenges. By expanding aquaculture, generating self-employment opportunities, and maintaining the protocol of sustainable development, trout farming may become a lifeline for rural areas. The concerned authority must be accountable for formulating effective policies for the promotion of trout farming for rural development.